Saga (2012), volume 11 ebook - Vaughan, Brian K. (Saga (2012), 2024)
While Hazel and her family fight for scraps to survive, the rich and powerful race to forge new allegiances in the universe's never-ending war. Romeo & Juliet meets Star Wars in this genre-blending, sci-fi/fantasy space opera about star-crossed lovers from enemy worlds. An epic for mature readers, SAGA follows new parents Marko and Alana as they risk everything to raise their child amidst a never-ending galactic war. A multiple award-winning, critically acclaimed masterpiece and one of the most iconic, bestselling comic book series of its time. The SAGA series has sold over 7 million copies to date across all formats, has been translated into 20 languages, and has garnered multiple Eisner and Harvey Awards, plus a Hugo Award, British Fantasy Award, Goodreads Choice Award, Shuster Award, Inkwell Award, Ringo Award, and more. It has been featured in such mainstream media outlets as TIME, Entertainment Weekly, The Atlantic, NPR, and beyond, and has become a pop culture phenomenon. Collects SAGA #61-66